What Would Confucius Do? – Confucian Ethics and Self-Regulation in Management - Woods, Peter; Lamond, David A. (2011)
We examined Confucian moral philosophy, primarily the Analects, to determine how Confucian ethics could help managers regulate their own behavior (self-regulation) to maintain an ethical standard of practice. We found that some Confucian virtues relevant to self-regulation are common to Western concepts of management ethics such as benevolence, righteousness, wisdom, and trustworthiness. Some are relatively unique, such as ritual propriety and filial piety. We identify seven Confucian principles and discuss how they apply to achieving ethical self-regulation in management. In addition, we examined some of the unique Confucian practices to achieve self-regulation including ritual and music. We balanced the framework by exploring the potential problems in applying Confucian principles to develop ethical self-regulation including whistle blowing. Confucian moral philosophy offers an indigenous Chinese theoretical framework for developing ethical self-regulation in managers. This is relevant for managers and those who relate to managers in Confucian-oriented societies, such as China, Korea, Japan, and Singapore. We recommend further research to examine if the application of the Confucian practices outlined here actually work in regulating the ethical behavior of managers in modern organizations.
Keywords: Self-regulation; management ethics; Confucian; Confucius; Analects